Analysis of Management Reserve and Schedule Slip in a Steel Truss Bridge Project - Dina Kurnia Shanty; I Nyoman Dita Pahang Putra; Elok Dewi Widowati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Project implementation delays (schedule slips) not only affect project completion time but may also influence the adequacy of the project’s cost reserve (management reserve). This study aims to analyze the relationship between schedule slip and management reserve using the Earned Value Analysis (EVA) approach through the Estimate at Completion (EAC) and Variance at Completion (VAC) parameters. The study utilized planned S-curves, weekly progress reports, and the project contract value as the Budget at Completion (BAC) from a steel truss bridge construction project with a planned duration of 35 weeks and an actual completion time of 36 weeks. EVA parameters were evaluated at each reporting period. The Actual Cost of Work Performed (ACWP) was determined using the Project Implementation Budget (Rencana Anggaran Pelaksanaan/RAP) approach at 90% of the contract value, while the management reserve was established at 10% of the BAC. The results demonstrate that schedule slip is directly associated with an increase in the EAC value, leading to a reduction in the VAC value toward the management reserve threshold. Conversely, improvements in schedule performance increased the VAC value above the management reserve limit, indicating that the project’s cost reserve remained secure. Although the project experienced a one-week delay at completion, the VAC value remained within the management reserve threshold, confirming that the management reserve was still adequate. These findings indicate that project delays significantly affect the dynamics of management reserve conditions through changes in the estimated final project cost. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 8: Decent Work and Economic GrowthSDG 11: Sustainable Cities and Communities